Relationship between Blood Pressure and Multimorbidity with Glomerular Filtration Rate (GFR) in Patients with Chronic Renal Failure - Ailsa Dzakiyah Dzahabiyah Hibatulloh; Fiora Ladesvita (Universitas Muhammadiyah Surakarta, 2023)
The prevalence of hypertension and chronic kidney disease continues to increase worldwide and has the potential to experience more significant cardiovascular disease. Older patients have also reported an association between a modest decrease in glomerular filtration rate (GFR) and an increase in systolic blood pressure. As the prevalence of chronic kidney disease (CKD) increases with age, multiple complications can occur, including hypertension, diabetes, and other cardiovascular diseases. Multimorbidity is defined as the condition of having two or more chronic morbidities. This study aims to evaluate the relationship between blood pressure and multimorbidity with the glomerular filtration rate (GFR) of chronic kidney failure patients at RST Dompet Dhuafa Parung, Bogor Regency. This research is a retrospective study with a cross-sectional design and using a consecutive sampling method. Data was taken from medical records on 112 samples of chronic kidney failure patients undergoing hemodialysis in the period January 2021 to March 2022. The results of the Spearman correlation test showed a p-value of 0.025 on the relationship between systolic blood pressure and GFR and a p-value of 0.008 on the relationship between diastolic blood pressure with GFR. At the same time, the results of the multimorbidity statistical test with GFR showed a p-value of 0.209. It can be seen that there is a relationship between systolic blood pressure and diastolic blood pressure with GFR, whereas there is no relationship between multimorbidity and GFR in patients with chronic kidney failure at RST Dompet Dhuafa Parung Bogor.